Long-Term Protection of CHBP Against Combinational Renal Injury Induced by Both Ischemia–Reperfusion and Cyclosporine A in Mice - Zhang, Yufang; Wu, Yuanyuan; Wang, Wei; Liu, Feng; Zhang, Yiwen; Yang, Cheng; Liu, Aifen; Wu, Jing; Zhu, Tongyu; Nicholson, Michael L.; Fan, Yaping; Yang, Bin (Frontiers in Immunology, 2021)
Renal ischemia–reperfusion (IR) injury and cyclosporine A (CsA) nephrotoxicity affect allograft function and survival. The prolonged effects and underlying mechanisms of erythropoietin derived cyclic helix B peptide (CHBP) and/or caspase-3 small interfering RNA (CASP-3siRNA) were investigated in mouse kidneys, as well as kidney epithelial cells (TCMK-1), subjected to transplant-related injuries. Bilateral renal pedicles were clamped for 30 min followed by reperfusion for 2 and 8 weeks, with/without 35 mg/kg CsA gavage daily and/or 24 nmol/kg CHBP intraperitoneal injection every 3 days. The ratio of urinary albumin to creatinine was raised by IR injury, further increased by CsA and lowered by CHBP at 2, 4, 6 and 8 weeks, whereas the level of SCr was not significantly affected. Similar change trends were revealed in tubulointerstitial damage and fibrosis, HMGB1 and active CASP-3 protein. Increased apoptotic cells in IR kidneys were decreased by CsA and CHBP at 2 and/or 8 weeks. p70 S6 kinase and mTOR were reduced by CsA with/without CHBP at 2 weeks, so were S6 ribosomal protein and GSK-3β at 8 weeks, with reduced CASP-3 at both time points. CASP-3 was further decreased by CHBP in IR or IR + CsA kidneys at 2 or 8 weeks. Furthermore, in TCMK-1 cells CsA induced apoptosis was decreased by CHBP and/or CASP-3siRNA treatment. Taken together, CHBP predominantly protects kidneys against IR injury at 2 weeks and/or CsA nephrotoxicity at 8 weeks, with different underlying mechanisms. Urinary albumin/creatinine is a good biomarker in monitoring the progression of transplant-related injuries. CsA divergently affects apoptosis in kidneys and cultured kidney epithelial cells, in which CHBP and/or CASP-3siRNA reduces inflammation and apoptosis.